2012
DOI: 10.5539/ijbm.v7n18p92
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Relationship between Service Quality in Primary Education and Parent Satisfaction

Abstract: The education is not only a major sector nowadays, but it is also an investment by parents for their children. This study aims to investigate the effect of the dimensions (reliability, tangibility, responsiveness, assurance and empathy) of service quality in primary education on parent satisfaction. This research is conducted in a public primary school and self-administered questionnaire is used to collect the related data. Data is collected based on SERVQUAL model through distributing 400 questionnaires to ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
4
6
0
Order By: Relevance
“…Five dimensions of service quality namely reliability, tangibles, responsiveness, assurance, and empathy were examined on their influence on parents' satisfaction. The result is consistent with the finding in Chen and Childhood (2016) and Incesu and Asikgil (2012), that is the reliability is significantly linked to the parents' satisfaction. It is observed in the findings that the parents value reliability the most as the private kindergartens are able to provide healthy and safe meals, promise things can complete on schedule, help children to resolve problems and faithfully inform parents about education information.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Five dimensions of service quality namely reliability, tangibles, responsiveness, assurance, and empathy were examined on their influence on parents' satisfaction. The result is consistent with the finding in Chen and Childhood (2016) and Incesu and Asikgil (2012), that is the reliability is significantly linked to the parents' satisfaction. It is observed in the findings that the parents value reliability the most as the private kindergartens are able to provide healthy and safe meals, promise things can complete on schedule, help children to resolve problems and faithfully inform parents about education information.…”
Section: Discussionsupporting
confidence: 92%
“…In the healthcare sector, assurance has a significant impact on patients by explaining that employees usually provide their clients with medical treatment, data sharing and clear medical understanding (Suki & Lian, 2011). Similar to the education sector, assurance has a significant impact on the parent's satisfaction (Incesu & Asikgil, 2012). This study indicated that parents attach great importance to the courtesy and trust of employees and teachers.…”
Section: Assurancementioning
confidence: 84%
See 3 more Smart Citations